Projection Of Climate Suitability For Mangosteen Based On Climate Change Scenarios In West Sumatra To Support National Resilience - Eka Alfred Sagala; Ernalem Bangun; Adi Subiyanto; Presly Panusunan Simanjuntak (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The West Sumatra Provincial Government began to improve the development of the plantation sector of mangosteen, because the mangosteen plant became a superior commodity in the Province of West Sumatra. In this regard, it is important to know the climate suitability of the mangosteen plant and its projections, which will be used to take development planning steps in the appropriate area and support the increase in exports of mangosteen plants in West Sumatra Province to support national resilience in the face of climate change. The data used were monthly rainfall observation data and monthly air temperature for the period 2006-2015 at 46 rain posts in West Sumatra Province. The Minangkabau Meteorological Station is used as a reference station for monthly air temperatures estimation in 45 other rain posts which were calculated using the Braak method. Besides, land physical data such as soil texture and slope were used in each district in West Sumatra Province. Projected data used the Representative Concentration Pathways (RCP) 4.5 scenario model for monthly air temperature and monthly rainfall from the Model for Interdisciplinary Research on Climate (MIROC5) model with resolutions up to 20 x 20 km in the period 2006-2040. The projection data was divided into the baseline period for 2006-2015 and the projection period of 2031-2040. The climate suitability period was made for the present period 2006-2015 and the future projections for the period 2031- 2040. The results showed that the area of West Sumatra Province for the Very Appropriate category (S1) was decreasing in the projection period of 2031-2040 compared to the 2006-2015 baseline period. This can be seen in the projection period of the Very Appropriate category (S1), the area was reduced to 2,584,234 ha (72%) while in the baseline period the Very Corresponding category (S1) reached 2,811,321 ha (78%).